Fakulta architektury, TU Dresden - Rosecká, Kristýna; Rosecká Kristýna (České vysoké učení technické v Praze, 2017)
Předmětem bakalářské práce je návrh fakulty architektury v centru kampusu TU Dresden. V budově se nachází velké ateliéry, které jsou umístěny do dvou věží otevírajících se do kampusu. Věže propojují učebny a kabinety tvořící horizontální hmotu. Parter je průchozí, otevřen do ulice kavárnou a výstavními prostory.

The subject of my bachelor thesis is project of faculty of architecture in the centre of Technical University in Dresden. Thera are big studios situated to two towers opened to the campus. The towers are connected by horizontal line created by classrooms and office rooms. The parterre is pass through opened to pedestrian street by café and gallery.
Faculty of Architecture, TU Dresden
Keywords: škola architektury,kampus,TUD,ateliér,fakulta architektury,Drážďany; school of architecture,campus,TUD,studios,faculty of architecture,Dresden